Analysis on factors affecting investment as an alternative earning of employees in CTRM Aero Composites Melaka / Muhammad Azfar Md Sadan and Noor Afifah Saari - Md Sadan, Muhammad Azfar; Saari, Noor Afifah (Faculty of Business and Management, 2013)
The study was conducted to find out the significant relationship between independent variables with dependent variable. The variables selected are investment return, individual knowledge, promotion and advertising, and saving for future. The dependent variable is investment as alternative earning. The method used for this study is the regression analysis. The result then has been interpreted base on the correlation, coefficient correlation, F-statistic and T- statistic. The data used for the study are collected for the period of January until July year of 2013. Base on the result, it was concluded that individual knowledge and saving for future are not significant toward the investment as alternative earning. However, there are significant relationship between investment return, promotion and advertising toward the investment as alternative earning.